Active Preservation at The Record Center of Padjadjaran University as a Steps to Extend The Life of The Archives - Windyani Aprilia; Dr. Ute Lies Siti Khadijah; Samson CMS; Lutfi Khoerunnisa (JPUA: Jurnal Perpustakaan Universitas Airlangga: Media Informasi dan Komunikasi Kepustakawanan, 2022)
Archives are important documents that function in administrative, legal, financial, organizational, historical, directive, and information functions in the realm of government. The importance of archives to be stored, preserved, and maintained is one of the reasons for writing this article. This paper describes the types of archives and the active preservation actions taken against conventional archives in the form of image sheet archives and photo archives carried out by the UPT Arsip (Record Center) Universitas Padjadjaran. This active preservation action is carried out as an effort to extend the life of archives or collections from archival institutions. The location of this research is at UPT Archives (Recording Center) Universitas Padjadjaran. This research was conducted by conducting direct observations at the UPT Archives (Record Center) Universitas Padjadjaran and conducting interviews. The research method was carried out using a qualitative descriptive method, namely by explaining the active preservation actions carried out by the UPT Archives (Recording Center) Universitas Padjadjaran. The actions taken by the UPT Arsip (Record Center) Universitas Padjadjaran are to maintain the temperature of the archives by coating the photos with tissue on each sheet and also cleaning the archives from dust. Files are also stored according to file type in roll o'packs, racks, or boxes to avoid damage to records due to dust. This article also discusses the lack of preservation efforts made by the UPT Archives (Record Center) Universitas Padjadjaran such as the amount of ventilation in the room which increases dust capacity.